Antibody Preparation, Protein Expression, and Function Analysis of Cyp19a1b in Ovarian Differentiation in a Natural Triploid Teleost Qi River Crucian Carp (Carassius auratus) - Yongjing Li; Yujiao Jin; Limin Wu; Xuejun Li (Fishes)
Estrogen is an essential sex steroid that functions in numerous biological systems including female reproduction, neuroendocrine, vascular, skeletal, and immune systems. The synthesis of estrogen is controlled by the rate-limiting enzyme, which has been confirmed to exist in two different forms, named brain aromatase and ovary aromatase, and encoded by cyp19a1a and cyp19a1b respectively in teleosts. However, existing studies have primarily focused on the expression and function of cyp19a1b in the brain and cyp19a1a in the gonad, the roles of cyp19a1b in the female gonad of teleosts are largely unknown. In our previous study, we cloned the full length of the cyp19a1b gene from a natural triploid teleost Qi River crucian carp (Carassius auratus), andthe spatial and temporal expression patterns of cyp19a1b mRNA were detected. To further clarify the roles of cyp19a1b in the ovarian differentiation of Qi River crucian carp, we produced a polyclonal antibody of Cyp19a1b in this study. Western blotting results showed that Cyp19a1b was mainly expressed in the brain and then in the ovary, heart, liver, and muscle. During embryogenesis, Cyp19a1b was abundantly expressed in the neurula stage. Immunohistochemistry demonstrated that Cyp19a1b was expressed in the radioactive glial cells (RGCs) of the brain from 20 days after hatching (dah) and the somatic cells of the ovaries from 30 dah, the critical period of ovarian differentiation in Qi River crucian carp. With the treatment of letrozole, an inhibitor of the aromatase, the expression of Cyp19a1b was downregulated both in the brain and gonad. Our results suggested that Cyp19a1b might be involved in the development of the nervous system and also participate in the ovarian differentiation of Qi River crucian carp.